Community forest, environment conservation and rural livelihood - Pokhrel, Rajendra Kumar; Pokhrel Gautam, Anju (Geographical Journal of Nepal, 2024)
The study analyses the economic benefit to rural people derived from the community forest and the role of community forest in the livelihood of the rural people. For this purpose, Khajure Community Forest of Dang district was selected. This article analyses interactions among economic development, the environment, and natural resource use pattern. Community forestry promotes sustainable management of forests by the local community for their collective benefits and promotes equal rights regardless of caste, ethnicity and gender. Community Forest Users’ Group highly depend on CF for their basic households needs such as fuel wood, grass, fodder and timber. Community participation in managing forest has contributed to forest conservation, scientific utilization of forest products and social inclusion which ultimately fosters community ownership in management and use of natural resources. But there are problems in CF governance and benefit sharing. The main issues of community forest are elite dominance in decision-making, social exclusion, and unequal benefit sharing. Rural people go through the exploitation of forest resource haphazardly for their survival. Exploitation of natural resources, including forest resource, contribute to global environmental problems and climate change. Electric cook stoves could be a good, clean fuel source while also helping to reduce the trade deficit. Scheduled firewood collection has resulted to shortage of fuel wood and has increased dependency on cow dung cake for daily cooking. Socio-economic condition of community members has remained as the obstacle for fuel shifting towards modern and clean energy that produces no smoke and no indoor air pollution, and thus, reducing respiratory diseases. Fuel transition has great positive impact on forest conservation,too.